2010
DOI: 10.1093/bja/aeq167
|View full text |Cite
|
Sign up to set email alerts
|

Repeat dosing of rocuronium 1.2 mg kg−1 after reversal of neuromuscular block by sugammadex 4.0 mg kg−1 in anaesthetized healthy volunteers: a modelling-based pilot study

Abstract: Rapid re-onset of NMB occurred after repeat dose of rocuronium 1.2 mg kg(-1) as early as 5 min after sugammadex in healthy volunteers. Re-onset of block took longer if second rocuronium dose was <25 min after sugammadex. The duration of action of second rocuronium dose increased with later repeat dose time points.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 13 publications
1
39
1
2
Order By: Relevance
“…3 Re-appearance of T1 in the present case was at 64 min, and the duration of action was not noticeably shortened. This outcome is not consistent with Cammu et al's results, 2 and the difference might be due to the anesthetics used. Sevoflurane has been reported to potentiate the effect of nondepolarizing NMBAs, 4 and in the present case, it may have prolonged the duration of action of re-administered rocuronium and potentiated it even a short time after sugammadex.…”
contrasting
confidence: 92%
See 1 more Smart Citation
“…3 Re-appearance of T1 in the present case was at 64 min, and the duration of action was not noticeably shortened. This outcome is not consistent with Cammu et al's results, 2 and the difference might be due to the anesthetics used. Sevoflurane has been reported to potentiate the effect of nondepolarizing NMBAs, 4 and in the present case, it may have prolonged the duration of action of re-administered rocuronium and potentiated it even a short time after sugammadex.…”
contrasting
confidence: 92%
“…2 They found that sugammadex prolongs the onset time of rocuronium when the time interval from sugammadex administration was \25 min. Our patient was given rocuronium 1.0 mgÁkg -1 , and T1 had not disappeared after 195 sec, indicating that this dose was insufficient under sevoflurane anesthesia to achieve complete NMB 19 min after sugammadex.…”
mentioning
confidence: 99%
“…13 The second is that too much sugammadex on board would limit the options should reintubation of the trachea or repeat surgery be needed shortly after the end of the case. 15,16 However, the concept of reversal of residual neuromuscular block with clinically limited dose range of sugammadex generated concern about reparalysis, arguing that sugammadex 1.0 mg/kg or 0.5 mg/kg is insufficient to restore the safety margin of the neuromuscular junction; thus, rebound of the block may happen. 17,18 Actually only a few studies have investigated the effect of low-dose sugammadex on the reversal of shallow residual neuromuscular blocks.…”
Section: Summary Of Resultsmentioning
confidence: 99%
“…5 Rocuronium can be re-administered five minutes after receiving sugammadex, but a slower onset and duration time should be expected due to the remaining sugammadex in circulation. [35][36][37] …”
Section: Dosingmentioning
confidence: 99%